Seroprevalence of contagious caprine pleuropneumonia in small ruminants in Karnataka, India - CHANDRASHEKAR, K M; KUMAR, G S NAVEEN; CHANDRASHEKHARA, N; PUNYA, J; RANGANATH, L (The Indian Journal of Animal Sciences, 2020)
The objective of this study was to investigate the prevalence of Contagious caprine pleuropneumonia (CCPP) in small ruminants in Hassan district, Karnataka, India and to evaluate the accuracy of Slide Agglutination Test (SAT) over competitive ELISA (cELISA) diagnostic methods. A total of 227 serum samples from apparently healthy goat and sheep were screened for CCPP antibodies by SAT and cELISA. The study revealed no significant difference in seroprevalence of CCPP with respect to species (Goat vs Sheep), sex (Male vs Female) and farms (Organised vs Unorganized), where as significant difference was noticed in age groups by both SAT and cELISA diagnostic methods. The prevalence of CCPP by SAT and cELISA in sheep were 31.81% and 41.55% and goat 30.14% and 38.35% respectively. Higher seroprevalence rate was observed in older animals of more than five years compared to less than five years age groups. The sensitivity, specificity and accuracy of SAT as compared with cELISA in CCPP diagnosis was 78.41%, 98.56% and 97.75% respectively. The results of this study indicated the endemicity of the CCPP infection in and around Hassan region of Karnataka state and further showed that SAT being economical with good sensitivity and accuracy can be effectively used in the absence of cELISA kits.